2016 Physics Education Research Conference Proceedings 2016
DOI: 10.1119/perc.2016.pr.059
|View full text |Cite
|
Sign up to set email alerts
|

Using RealTime Physics with different instructional technologies in a circuits lab

Abstract: Prior physics education studies have established a positive influence in learning when students use researchbased strategies (mainly Tutorials) and instructional technologies in physics courses. This contribution studies learning outcomes and behavior when combining a research-based strategy that promotes collecting data, RealTime Physics (RTP), with different instructional technologies: 1) RTP using probes and computers (original version), 2) RTP with probes and a graphing calculator, and 3) RTP with PhET sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The chosen items are focused on current, voltage and circuits configuration. These items were retrieved in Spanish from a previous publication [13]. We used part of the DIRECT to evaluate only the topics that were addressed in the activities.…”
Section: Pre/post-testmentioning
confidence: 99%
“…The chosen items are focused on current, voltage and circuits configuration. These items were retrieved in Spanish from a previous publication [13]. We used part of the DIRECT to evaluate only the topics that were addressed in the activities.…”
Section: Pre/post-testmentioning
confidence: 99%
“…Regarding those mentioned above, it has been widely documented that university students require a broad set of skills to be successful in their careers. For example, it has been shown that collaborative work helps students to promote conceptual learning, develop communication skills, foster interdependence among peers, and generate a positive classroom environment [6][7][8].…”
Section: Introductionmentioning
confidence: 99%